The Effectiveness of Discovery Learning Model Based on Sparkol Videoscribe and Chart on Economic Learning Outcomes - Anggraeni, Oki; Prasetyo, P. Eko; Thomas, Partono (Universitas Negeri Semarang, 2020)
Audio visual-based learning is a media that is concerned with hearing and vision. In era 4.0 the effective and efficient media-based learning are needed. The study is aimed to explain the effectiveness of the discovery learning model based on Sparkol Videoscribe and Chart on students learning outcomes in Economics, as well as looking at the influence of economic learning interest in class XI IPS students on their learning outcomes. This research design was comparative quantitative with the quasi-experiment approach. The object of this research was studentsâ€™ learning model of SMA Negeri 1 Randudongkal, Pemalang, Central Java. The level of effectiveness analysis techniques used t-test and N-Gain. The results showed that the experimental class had higher economic learning outcomes than the control class with a t-test value of 70.22 and an experimental class of 75.61. The variables of students learning interest-based on simple regression tests the results stated that 0.207 â‰¥ 0.05 then Ho was accepted Ha was rejected, it meant that there was no effect on the economic learning outcomes of students of XI IPS at SMA Negeri 1 Randudongkal.